Familial Hypercholesterolemia: Genetics, Symptoms, Diagnosis and Treatment - A Literature Overview - Maciej Rutkiewicz; Sabina Przygodzka; Katarzyna Gadżała; Karolina Garbino; Katarzyna Brudniak; Antoni Szuścik; Magdalena Czyczerska (Quality in Sport)
Familial hypercholesterolemia is a genetic disorder of lipid management, especially LDL-C. It's inherited autosomal dominant in most cases. The illness is characterized by high, low-density lipoprotein cholesterol (LDL-C) levels. According to many researchers, the frequency of prevalence is estimated at 1:200 in the global population. Many studies showed that illness is underdiagnosed and therefore undertreated. There are three known genes coding three different proteins, and changes are in charge of wrong lipid management. These are: LDL-Receptor (LDLR), Apolipoprotein B (ApoB), and Proprotein convertase subtilisin/kexin 9 (PCSK9). People who are affected by mutation have around thirteen times higher risk of coronary artery disease (CAD) and, in order to that, premature death. Identifying sickness includes a physical examination, when we can observe xanthomas, corneal arcus, or xanthomata, and scales that focus on the patient's as well as his family's past. A definite diagnosis can be approved by genetic testing, which shows a causable mutation.